PENGARUH IMPLEMENTASI PENGGUNAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) TERHADAP KUALITAS PENDIDIKAN DI SMAN 1 BLAMBANGAN UMPU KABUPATEN WAY KANAN - . Winingsih (Universitas Bandar Lampung (UBL), 2016)
The Government generally provides Operational Assistance Funds schools high school to realize the service quality and affordable education for all walks of life, the existence of government assistance provided so that frees school education costs or relieve the Bills school fees and also so that the quality of the learning process in schools will be increased. Based on the purpose of the research is to find out and menganalisi the influence of the implementation of the use of the operational grant School to quality high school 1 Blambangan Umpu Way Kanan.This research uses descriptive quantitative analysis design, with the implementation of the use of the operational grant School made an independent variable and the dependent variable as a quality education. The samples used in the study amounted to 50 respon dents with a random method of proportionally (proportional random sampling). The analysis used a test validity, reliability test and analysis of simple linear regression.Based on the results of the study can then note that: (1) implementation of the use of the operational grant School signfikan positive effect on quality High school 1 Blambangan Umpu Way Kananit looks from the supporting indicators or indicators with highest value i.e. the bureaucratic structure (bureaucratic structure) and the indicators are hampered or having the lowest score is the disposition (disposition). (2) aspects that become advocates and a barrier to the implementation of the use of the operational grant school to quality High school 1 Blambangan Umpu Way Kanan, among other things: (a) aspects that become advocates namely good sinergisitas between the school committee, the principal as well as educators in making the school budget plan and management of the operational grant school, (b) restricting aspects namely the hassle in the preparation of the report of the accountability, delay in disbursement, the decline in educational services in particular extracurricular activities and less pahamnya society Keywords: School Operational Assistance, The Quality of Education